The Geological study of the sea bottom and subbotom and the recent research trends (with emphasis on the continental shelf area) - ΠΕΡΙΣΟΡΑΤΗΣ Κ. (Bulletin of the Geological Society of Greece, 2002)
The systematic research of the sea bottom started axcually only in the 19th century with the research voyage of the British ship "CHALLENGER" but was particularly developed during the early 20th century. The Greek seas were geologically explored after 1950, with the research trip of the R/V Verna in 1954 in Korinthiakos Gulf. Since then a great number of research programs has been carried out in the Greek Seas both in the shelf and the deep sectors in which the Greek scientists have played a major role. The major factor in shaping the todays shelf morphology is sedimentation controlled mainly by the sea level changes during Quaternary. The shelf break in the Aegean and Ionian seas lies at a depth of 120m. to 160m. and is usually covered by relict sediments and locally by holocenic sediments, particularly at the deltaic areas. In low sea level stands many of the todays gulfs were subaerically exposed or constituted lakes of variable depth with or without outlets toward the open sea. During these stages coarse sediments were deposited mainly beyond the shelf break. During high sea level stages the coarse sediments were deposited on the shelf and the fine grained ones surpassing the self break were deposited in the deep areas. Theses changes in sediment texture are reflected in the deep sea seismic profiles as alternating opaque-transparent layers. Although the Greek area is characterized by high seismic and tectonic activity, tectonism and eustatic/isostatic factors played a considerably minor role in shaping the shelf morphology that of sea level changes. The study of the shelf area during the various sea level stands helped in locating occurrence of placer deposits in the Northern Aegean shelf and in recognizing the trans gressional layer as a suitable horizon for foundation of civil engineering projects. Except these, the shelf studies contributed important information to the basic geological knowledge. Examples from condribution to geoarchaeology to biogeography are cited. Regarding the future research trends in Marine Geology, these can be: The development of marine data (metadata) bases. The systematic use of multibean systems. The further development of digital processing of the seismic reflection records. The collection of data for the anticipating future climatic changes. The assessment of the eventual catastrophic events in the coastal zone. The recording in real time of the active sedimentation parameters.